Effect of market age on production of goat meat and skin (Bangladesh Journal of Animal Science, 2013)
The effect of marketing of goats at different ages on the yield of carcass and skin as well as economic impact were investigated. Landless and marginal farmers sold their goats 4 to 6 months earlier at 54 and 104%, 3 and 5%, 67 and 127% less weight, dressing percentage and carcass yield, respectively less than small and medium farmers; and on average 36% less in small farmers than medium farmers. Estimated skin size of the goats belonged to landless and marginal farmers was 75% and 133% less than goats sold by small and medium farmers; and 33% less in small farmers than medium farmers. An estimated goat slaughtered per year was 7.14, 5.44 and 4.28 million at the age of 6, 10.5 and 15.5 months, respectively and the yield of meat and skins was 23.28, 31.99 and 31.67 million kg and 10.71, 15.46 and 14.98 million sqft, respectively. It is estimated that if goats are raised up to 15.5 months of age to higher weight of 17.10 kg may provide additional 41.08 million kg meat and 19.4 million sqft skins and their present market values would be Taka 14377 and 873 millions, respectively at the present subsistence level of goat farming and marketing systems in the country. DOI: http://dx.doi.org/10.3329/bjas.v42i1.15785 Bang. J. Anim. Sci. 2013. 42 (1): 67-70